208k views
5 votes
Write out the steps that you would follow to solve the equation: 3(x-4) = 2x +5

User Mark Fondy
by
5.7k points

2 Answers

1 vote

Answer:


\displaystyle \rm \longmapsto \:3(x - 4) = 2x + 5


\displaystyle \rm \longmapsto \:3x - 12 = 2x + 5

  • Subtract 2x from the both sides:


\displaystyle \rm \longmapsto 3x - 2x - 12 = 2x - 2x + 5


\displaystyle \rm \longmapsto x - 12 = 5

  • Add 12 to the both sides:


\displaystyle \rm \longmapsto x - 12 + 12 = 5 + 12


\displaystyle \rm \longmapsto x = 15

User RePierre
by
5.1k points
4 votes

Answer:

x = 17

Explanation:

To solve this equation, we can illustrate the algebraic concepts being employed and solve for the variable.

3(x - 4) = 2x + 5 Distribute the 3 into the parentheses.

3x - 12 = 2x + 5 Subtract 2x from both sides of the equation to combine like terms.

x - 12 = 5 Add 12 to both sides of the equation.

x = 17

User Akira Fukushima
by
4.9k points